An investigation of the quantitative and qualitative shipping market research and forecasting methods and their strategic applications to liner shipping and tramp shipping (VLCC sector) - Zhang, Hongzhou (2009)
Due to the ongoing uncertainty of shipping market and especially the volatile nature of freight rates, the shipping community is always interested in forecasting future earnings either based on their own knowledge and experiences about shipping, or through application of quantitative methods. The aim of this report is to carry out a thorough study and investigation of the qualitative and quantitative forecasting and research methods used by industry professionals or suggested by the scholars so as to develop a new forecasting framework with a comprehensive integration of these methods. We intend to use the framework to forecast the future freight earnings of liner shipping. The framework utilizes wide range of forecasting methods which include both qualitative and quantitative methods. Qualitative methods consist of System Dynamic, Jury of Executive Opinion and Market Sentiment Analysis; whereas quantitative methods comprise of Linear Regression, Multiple Regressions, Box Jenkins and Artificial Neural Network. These methods are well integrated based on Econometric Forecasts, Rule Based Forecasts, and Combined and Revised Forecasts models.